2022
DOI: 10.5539/jas.v14n10p12
|View full text |Cite
|
Sign up to set email alerts
|

Moringa (M. oleifera) Leaf Meal in Diets for Broilers and Laying Hens: A Review

Abstract: The cost of feed ingredients in poultry production is constantly increasing and it is one of the main constraints globally and especially in low income countries. As a consequence, scientists search for cheap and available sources of feed protein. The M. oleifera leaves have not only high protein but also excellent nutritive and biological properties. This review summarises results and findings of research related to the application of M. oleifera leaf as source of feed protein in broiler and egg production. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…ESPM values also went on the same trend as NH3 concentration value in which by supplementing moringa leaves (treatment C) on field grass produced the highest ESPM value (32.4 g N/kg DOMR) followed by treatments E, D, B and A (30.2, 28.5, 24.6 and 19.4 mg N/kg DOMR respectively). [13] stated that the protein in Moringa has good rumen bypass properties and in the study of [14] showed that by feeding dairy cows 2 kg or 3 kg DM of Moringa leaves increased milk yield (4.9 and 5.1 kg/day) compared to cows fed only Brachiaria brizantha hay; this improvement was related to an increase in feed intake and in the digestibility of nutrients (dry matter, organic matter, crude protein, and dietary fibre) in Moringa leaves.…”
Section: Ivgp Dmd Omd Rumen Nh3 and Empsmentioning
confidence: 99%
“…ESPM values also went on the same trend as NH3 concentration value in which by supplementing moringa leaves (treatment C) on field grass produced the highest ESPM value (32.4 g N/kg DOMR) followed by treatments E, D, B and A (30.2, 28.5, 24.6 and 19.4 mg N/kg DOMR respectively). [13] stated that the protein in Moringa has good rumen bypass properties and in the study of [14] showed that by feeding dairy cows 2 kg or 3 kg DM of Moringa leaves increased milk yield (4.9 and 5.1 kg/day) compared to cows fed only Brachiaria brizantha hay; this improvement was related to an increase in feed intake and in the digestibility of nutrients (dry matter, organic matter, crude protein, and dietary fibre) in Moringa leaves.…”
Section: Ivgp Dmd Omd Rumen Nh3 and Empsmentioning
confidence: 99%
“…Its immature fruit (pods) are green in color, 10-60 cm in length, contain 15-20 seeds, and at maturity change color to brown. The shape of a dry seed is round or triangular and it is covered by a light woody shell with papery wings; each tree can produce between 15,000 and 25,000 seeds annually (Paliwal et al, 2011;Su and Chen, 2020;Amad and Zentek, 2022) depending on the variety. Moringa oleifera can be propagated by direct seedlings, cuttings, or by seeds under minimal care and with a wide range of management practices (Paliwal et al, 2011).…”
Section: Biological Characteristics Of M Oleifera and Its Cultivationmentioning
confidence: 99%
“…It must be emphasized that stems and immature pods of M. oleifera have lower nutrient levels compared to leaves. The leaves of Moringa contain approximately 27-30% or slightly more protein on a dry matter (DM) basis, with significant quantities of all the essential amino acids (Amad and Zentek, 2022). The protein content of Moringa leaf meal is higher than that of other forage plants such as Medicago sativa (Alfalfa) and many commonly consumed green leafy vegetables (spinach and mint).…”
Section: Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…M. oleifera leaf products effectively prevented hypercholesterolemia and lipid deposition in mice by down-regulating plasma low-density lipoprotein cholesterol (LDL-C), triglyceride (TG), and total cholesterol (TC) levels [29,30]. The active phenolic and flavonoid substances in MO exhibit anti-lipid peroxidation effects and act as oxygen radical scavengers to protect the meat from oxidation [31]. The antioxidant properties of M. oleifera leaf were also reported to improve goat meat quality (chemical composition, color, and lipid stability) [32].…”
Section: Introductionmentioning
confidence: 99%